Educa????o de Jovens e Adultos (EJA): um estudo sobre a inclus??o de adolescentes no Centro Integrado de Educa????o de Jovens e Adultos (CIEJA) - Toledo, Ana Luiza Bacchereti Sodero de (2017)
The purpose of our research was to know the reasons that lead teenagers to go to regular school, especially in the eighth and ninth grade of elementary school, and what perspectives and expectations arise when they seek enrollment in the Integrated Center for Youth and Adult Education - CIEJA. The theoretical reference that guided us was dialectical historical materialism, because it is a dynamic and transitory object of study, presenting situations of contradictions and overcoming, necessary in the construction of the identity of the adolescent. We seek to know the history of Youth and Adult Education, we discuss adolescence, in its sui generis condition of learning, as well as reflect on the curriculum in Youth and Adult Education. From the methodological point of view, we used the qualitative-quantitative approach, through questionnaires and semi-structured interviews, with the triangulation of the data obtained by the Discourse Analysis and Statistical Analysis technique.